Research Skills Assessment of Teacher Education Students in Dagupan City - Gloria N Paragas; Maan L Ferrer; Angelica G Perez; Linda P Tello (ASEAN Journal of Basic and Higher Education, 2021)
This study aimed to assess how the Methods of Research course would improve the research skills of teacher education students by comparing their research skills before and after taking the said course. This study utilized an explanatory sequential mixed method research design where the researchers gathered and analyzed quantitative data then further conducted qualitative research to help explain the quantitative part in more detail. Quantitative data were analyzed through statistical analysis, whereas qualitative data were utilized as explanatory statements for the findings of the study. Findings reveal that the students had the medium ability on various research skills before taking up their Methods of Research course; but after one semester of being enrolled in the course, the students improved and showed high ability. Overall, the levels of research skills of the students before and after they took the course exhibited a significant increase in most of the required skills. This implies that the students had considerable improvement in their research skills after taking up the Methods of Research course. The researchers conclude that there was a significant improvement in the research skills of the teacher education students after the course. Factors that highly influenced the participants' improvement in their research skills were teaching strategies apt to the students' learning styles, strengths, and weaknesses, interest and self-confidence, and time management. Thus, this study recommends the Methods of Research instructors utilize innovative teaching strategies that will adjust to the strengths and weaknesses of the students to improve their learning on research.